Reverse Engineering: A New Well Monitoring and Analysis Methodology Approaching Playing-Back Drill-Rate Tests in Real-Time for Drilling Optimization - Nascimento, Andreas [UNESP]; Elmgerbi, Asad; Roohi, Abbas; Prohaska, Michael; Thonhauser, Gerhard; Gonçalves, Jose Luiz; Mathias, Mauro Hugo [UNESP] (ASME International, 2017)
Different researches have been developed during the past years aiming addressing challenges still faced in petroleum exploration. Rate of penetration and specific energy studies have been the main focuses in trying to boost operational efficiency. The combination of both techniques accomplished with a preoperational test (drill-rate test) may allow as a new trending tool the best side of the drillability optimization to take place. Further, by having these implemented in real-time, an interesting methodology result in seeing the penetrating processes as a step-by-step where drilling mechanics parameters can be more dynamically adjusted. Thus, the main focus of this paper is to address a combination of rate of penetration together with a specific energy formulation in parallel with a possible dynamic and real-time drill-rate test plotted graphs for sake of the drilling optimization enhancement.